Engineering the future of medicine: Natural products, synthetic biology and artificial intelligence for next‐generation therapeutics - Emre F. Bülbül; Helge B. Bode; Steven Schmitt; Kenan A. J. Bozhüyük (Clinical and Translational Medicine)
Abstract The eXchange Unit between Thiolation domains approach and artificial intelligence (AI)‐driven tools like Synthetic Intelligence are transforming nonribosomal peptide synthetase and polyketide synthase engineering, enabling the creation of novel bioactive compounds that address critical challenges like antibiotic resistance and cancer. These innovations expand chemical space and optimize biosynthetic pathways, offering precise and scalable therapeutic solutions. Collaboration across synthetic biology, AI, and clinical research is essential to translating these breakthroughs into next‐generation treatments and revolutionizing drug discovery and patient care.